Penerapan Promosi Jasmine Laundry Melalui Platform Sosial Media Yang Efektif - Hesniati, Hesniati; Sonata, Vina (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
UMKM are businesses that are established using limited and low capital. Jasmine Laundry is an UMKM engaged in laundry services. The problem faced by Jasmine Laundry is the lack of visibility and accessibility in the digital world. Currently, this business does not have a profile on Google Maps and social media accounts. The target activities to be carried out for partners are to create social media accounts and then make interesting and informative posts, so that customers can easily find and understand the services that Jasmine Laundry offers. techniques used are interviews and observations After the implementation of digital marketing, Jasmine Laundry UMKM felt significant benefits, especially in terms of increasing the number of followers and customers who came.